Application of the Grey System Theory in Construction Management: A Case Study of Construction Paint Supplier Evaluation and Selection Criteria - Pham, C. P.; Nguyen, P. T.; Phan, P. T. (Engineering, Technology & Applied Science Research, 2022)
Material management is an important task in building construction. They account for a substantial proportion of investment capital and construction volume. However, as material prices are often affected by the market, choosing the right construction supplier is not an easy decision for contractors, especially for those materials required during the finishing phase of the construction. As one of these finishing materials is paint, identifying core criteria for evaluating and selecting the best construction paint supplier is a crucial economic choice for construction contractors. Assessing the importance of these criteria is a complex multi-criteria decision-making problem. To reflect the risks and uncertainties in this problem, the current paper presents a grey system theory approach to prioritize important criteria for selecting paint material suppliers in construction projects.